"All-crystalline" phase transition in nonmetal doped germanium–antimony–tellurium films for high-temperature non-volatile photonic applications. (15th April 2020) - Hu, Chaoquan; Yang, Zhongbo; Bi, Chaobin; Peng, Hongyan; Ma, Liang; Zhang, Chengchao; Gu, Zhiqing; Zhu, Jiaqi
Abstract: Phase-change materials have attracted much attention in the past three years due to its wide applications in non-volatile optical fields. Although the amorphous-cubic phase transition of Ge2 Sb2 Te5 is used most commonly, it has problems such as poor thermal stability and large density variation because the amorphous phase is metastable and of low density. Since these issues have not been well addressed, non-volatile optics are currently limited to applications in mild environments (≤120 °C). In this paper, we replace the traditional phase transition (amorphous-cubic phase) with the "all-crystalline" phase transition (cubic-hexagonal phase) that has been ignored in the past, achieving combination of high optical contrast ( ΔR =10.3%), high thermal stability ( TL = 240 °C) and ultra-small density variation ( Δρ = 0.5%). The maximum service temperature of non-volatile optics increases from 120 to 240 °C. Our results from experiments, theoretical calculations and spectral fittings are in good agreement, proving that the key to achieve "all-crystalline" phase transition with high optical contrast is to increase the difference in structural disorder between cubic and hexagonal phases. An effective method for increasing this disorder difference is the small atom (N or C) doping rather than large atom (Ag) doping that previously thought. The new insights have been well explained by discussing relationships among doping, formation energy, structural disorder and optical contrast. Therefore, our research not only proposes new methods and mechanisms for achieving high-performance "all-crystalline" phase transition, but also extends the applications of non-volatile optical devices from mild to high-temperature environments in the fields of aerospace and military. Graphical abstract: Image, graphical abstract